Inhibition of ATM reverses EMT and decreases metastatic potential of cisplatin-resistant lung cancer cells through JAK/STAT3/PD-L1 pathway - Mingjing Shen; Zhonghua Xu; Weihua Xu; Kanqiu Jiang; Fuquan Zhang; Qifeng Ding; Zhonghen Xu; Yongbing Chen (Journal of Experimental & Clinical Cancer Research, 2019)
Abstract Background The cisplatin-resistance is still a main course for chemotherapy failure of lung cancer patients. Cisplatin-resistant cancer cells own higher malignance and exhibited increased metastatic ability, but the mechanism is not clear. In this study, we investigated the effects of Ataxia Telangiectasia Mutated (ATM) on lung cancer metastasis. Materials and methods Cisplatin-resistant A549CisR and H157CisR cell line were generated by long-term treating parental A549 and H157 cells (A549P and H157P) with cisplatin. Cell growth, cell migration and cell invasion were determined. Gene expressions were determined by Western Blot and qPCR. Tumor metastasis was investigated using a xenograft mouse model. Results The IC50 of the cisplatin-resistant cells (A549CisR and H157CisR cells) to cisplatin was 6–8 higher than parental cells. The A549CisR and H157CisR cells expressed lower level of E-cadherin and higher levels of N-cadherin, Vimentin and Snail compared to the parental A549P and H157P cells, and exhibited stronger capabilities of metastatic potential compared to the parental cells. The ATM expression was upregulated in A549CisR and H157CisR cells and cisplatin treatment also upregulated expression of ATM in parental cells, The inhibition of ATM by using specific ATM inhibitor CP466722 or knock-down ATM by siRNA suppressed Epithelial-to-Mesenchymal transition (EMT) and metastatic potential of A549CisR and H157CisR cells. These data suggest that ATM mediates the cisplatin-resistance in lung cancer cells. Expressions of JAK1,2,、 STAT3 、PD-L1 and ATM were increased in A549CisR and H157CisR cells and could by induced by cisplatin in parental lung cancer cells. Interestedly, ATM upregulated PD-L1 expression via JAK1,2/STAT3 pathway and inhibition of ATM decreased JAK/STAT3 signaling and decreased PD-L1 expression. The treatment of PD-L1 neutralizing Ab reduced EMT and cell invasion. Inhibition of JAK1,2/STAT3 signaling by specific inhibitors suppressed ATM-induced PD-L1 expression, EMT and cell invasion. Importantly, inhibition of ATM suppressed EMT and tumor metastasis in cisplatin-resistant lung cancer cells in an orthotopic xenograft mouse model. Conclusions Our results show that ATM regulates PD-L1 expression through activation of JAK/STAT3 signaling in cisplatin-resistant cells. Overexpression of ATM contributes to cisplatin-resistance in lung cancer cells. Inhibition of ATM reversed EMT and inhibited cell invasion and tumor metastasis. Thus, ATM may be a potential target for the treatment of cisplatin-resistant lung cancer.